Autoimmune amelogenesis imperfecta in patients with APS-1 and coeliac disease - Gruper, Yael; Wolff, Anette S B; Glanz, Liad; Spoutil, Frantisek; Marthinussen, Mihaela Cuida; Osickova, Adriana; Herzig, Yonatan; Goldfarb, Yael; Aranaz-Novaliches, Goretti; Dobeš, Jan; Kadouri, Noam; Ben-Nun, Osher; et al. (Nature, 2023)
Ameloblasts are specialized epithelial cells in the jaw that have an indispensable role in tooth enamel formation-amelogenesis1. Amelogenesis depends on multiple ameloblast-derived proteins that function as a scaffold for hydroxyapatite crystals. The loss of function of ameloblast-derived proteins results in a group of rare congenital disorders called amelogenesis imperfecta2. Defects in enamel formation are also found in patients with autoimmune polyglandular syndrome type-1 (APS-1), caused by AIRE deficiency3,4, and in patients diagnosed with coeliac disease5-7. However, the underlying mechanisms remain unclear. Here we show that the vast majority of patients with APS-1 and coeliac disease develop autoantibodies (mostly of the IgA isotype) against ameloblast-specific proteins, the expression of which is induced by AIRE in the thymus. This in turn results in a breakdown of central tolerance, and subsequent generation of corresponding autoantibodies that interfere with enamel formation. However, in coeliac disease, the generation of such autoantibodies seems to be driven by a breakdown of peripheral tolerance to intestinal antigens that are also expressed in enamel tissue. Both conditions are examples of a previously unidentified type of IgA-dependent autoimmune disorder that we collectively name autoimmune amelogenesis imperfecta.
Keywords: Autoantibodies; antigeny; Humans; Ameloblasts; proteiny; střeva; Intestines; Proteins; ameloblasty; Antigens; lidé; Amelogenesis Imperfecta; Immunoglobulin A; AIRE Protein; zubní sklovina; celiakie; autoprotilátky; autoimunitní polyglandulární syndromy; Celiac Disease; imunoglobulin A; Dental Enamel; amelogenesis imperfecta; protein AIRE; Polyendocrinopathies, Autoimmune